2006
DOI: 10.1152/japplphysiol.00359.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in normobaric hypoxia in endurance runners. III. Muscular adjustments of selected gene transcripts

Abstract: We hypothesized that specific muscular transcript level adaptations participate in the improvement of endurance performances following intermittent hypoxia training in endurance-trained subjects. Fifteen male high-level, long-distance runners integrated a modified living low-training high program comprising two weekly controlled training sessions performed at the second ventilatory threshold for 6 wk into their normal training schedule. The athletes were randomly assigned to either a normoxic (Nor) (inspired O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
5
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(233 citation statements)
references
References 61 publications
17
201
5
10
Order By: Relevance
“…Even though no clear conclusions can be drawn on the beneficial effects of hypoxic training on HDL, it can be concluded that hypoxic training does not increase LDL levels, evident by none of the studies recording any significant increase in LDL levels. In theory, triglycerides level should reduce due to lipid oxidation through the transcriptor coactivator PGC1α [42] that is controlled by hypoxia inducible factor -1 that is activated during exposure to hypoxia. However, this has not been demonstrated in studies reviewed, as seen in mixed results obtain.…”
Section: Cholesterol Levelsmentioning
confidence: 99%
“…Even though no clear conclusions can be drawn on the beneficial effects of hypoxic training on HDL, it can be concluded that hypoxic training does not increase LDL levels, evident by none of the studies recording any significant increase in LDL levels. In theory, triglycerides level should reduce due to lipid oxidation through the transcriptor coactivator PGC1α [42] that is controlled by hypoxia inducible factor -1 that is activated during exposure to hypoxia. However, this has not been demonstrated in studies reviewed, as seen in mixed results obtain.…”
Section: Cholesterol Levelsmentioning
confidence: 99%
“…Increases blood serotonin levels [51] Ventilatory response during exercise increased [54] Normalises blood pressure [12,124] Improves insulin sensitivity [87] Appetite is suppressed [126,156] Improves respiratory function [68] Cardiovascular protection [155,163] Increases glucose transporter GLUT-4 [33,34] Increases body weight loss [84] 30 …”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…This fact increases the oxygen transport capacity of blood, due to the increase in erythropoietin hormone (EPO), hemoglobin (Hb) and erythrocytes, which improve both oxidative metabolism (15,31) and anaerobic performance (12) due to an increase in muscle buffer capacity (10) and an increase in the enzymes activity (21).…”
mentioning
confidence: 99%